More texts from the archive of Socrates: papyri from house 17, level B, and other locations in Karanis (P. Cair. Mich. III) - El-Maghrabi, Mohamed Gaber and Römer, Cornelia (45, 2021)
Frontmatter -- Table of Content -- Preface -- Introduction -- A. Literary Texts from House B17 and its Environment -- B. Documentary Texts from House B17 and its Environment -- C. Documents from Other Locations in Karanis -- Bibliography -- Indexes
https://katalog.fid-bbi.de/Record/183-1761268570